Quality assurance evaluation for National Universities Commission, Nigeria - Bolaji, Bojuwon Yusuf (Kulliyyah of Education, International Islamic University Malaysia, 2014)
The objective of this research is to develop and validate a proposed alternative Quality Assurance Evaluation (QAE) for National Universities Commission (NUC) of Nigeria by focusing on the psychometric properties of the measurement scale. This research employs a quantitative approach using the survey questionnaires that are adapted and adopted from the existing QAE and review of the literature. A sample size of 1,600 that comprised the vice-chancellors, staff, teaching staff, non- teaching staff, director/deans/HODs, NUC staff and students are used for this research. A seven-point likert scale is used to collect data from sixteen universities in the north central geopolitical zone of Nigeria. In the course of developing and validating the alternative QAE measurement scale, this research employed various steps that are considered particularly for principal component analysis (PCA), exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) for all constructs; input process (IP₂), leadership characteristics of leaders (LCL) and stakeholder contribution (SCON). A combination of a statistical techniques particularly structural equation modeling (SEM) and statistical package for social science (SPSS) software are used extensively in the stages involved. The findings of this research reveal that all constructs of alternative QAE (IP₂, SCON and LCL) are duly representative of each dimensional construct. It is also found that there is a very significant correlation between the alternative QAE constructs which resulted in the convergent, discriminant validity. All research questions and hypothesis of the research were successfully addressed and tested using appropriate data analysis and statistical techniques. The results shows that all the five hypotheses set for the study were accepted. Finally, the research also reveals that all determinants of the dimensional constructs for the proposed alternative QAE fulfilled the accreditation standards in measuring the quality of the universities in Nigeria. A major implication from the findings of this research is that, it would be able to make all the university fraternity in Nigeria understood that the existing QAE is lacking and no longer viable and appropriate in accrediting the university programmes. This research has prudently contributed a new knowledge empirically with regards to the three - factors solution (instead of only one for the existing (QAE) of the alternative QAE accreditation scale for NUC programmes, and first of its kind in the history of Nigeria's higher education.